Long-term treatment of patients with idiopathic pulmonary fibrosis with nintedanib: results from the TOMORROW trial and its open-label extension - Richeldi, Luca; Kreuter, Michael; Quaresma, Manuel (Thorax, 2018)
The TOMORROW trial of nintedanib comprised a randomised, placebo-controlled, 52-week period followed by a further blinded treatment period and an open-label extension. We assessed outcomes across these periods in patients randomised to nintedanib 150 mg twice daily or placebo at the start of TOMORROW. The annual rate of decline in FVC was −125.4 mL/year (95% CI −168.1 to −82.7) in the nintedanib group and −189.7 mL/year (95% CI −229.8 to −149.6) in the comparator group. The adverse event profile of nintedanib remained consistent throughout the studies. These results support a benefit of nintedanib on slowing progression of idiopathic pulmonary fibrosis beyond 52 weeks.